Introduction: Cultural Memory, the Past and the Static of the Present - Law, Jane Marie Marie (Acta Orientalia Vilnensia, 2006)
Ithaca, New York, September 2007“The past is not dead. In fact, it is not even past.”WILLIAM FAULKNERThe burgeoning field of study loosely known as “cultural memory studies” fills a strange gap between more traditional historiography and the anthropology of memory. Historiography in the more traditional sense embraces the stance that the past is knowable, verifiable to the extent that we have reliable evidence, and retrievable to some extent. It concerns itself with what happened in the past (and the many complications of knowing that). Cultural memory studies, on the other hand, address what Paul Ricoeur so aptly labeled “the mnemonic phenomenon,” the dialogical process through which collectivities recall the past in light of present concerns that arein part shaped by this very past that is being recalled and refashioned in the present. For the scholar of cultural memory, the object of study is not the past, but the many projects memory undertakes: healing, denial, revision, invention, recreation and re-creation, forgetting. What is the relationship between history and memory? What should it be?...